Pengaruh Model Pembelajaran dan Kecerdasan Interpersonal Terhadap Hasil Belajar Sejarah Siswa SMA Negeri 3 Kabupaten Tangerang - Eka Sari Handayani (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2017)
This research aims to know the effect of instructional model and interpersonal intelligence to history learning outcomes in SMA Negeri 3 Kabupaten Tangerang. This research is a quantitative research using experimental methods of treatment by level 2x2 design. Research instrument for measuring intepersonal intelligence is a questionnaire and Reseach instrument for measuring history learning outcomes is a multiple choice test. Population of research is all of student of SMAN 3 Kabupaten Tangerang. Sample of research are all student class XI IIS 2 and XI IIS 4. The results showed that: (1). History learning outcomes of students who use instructional model Talking Chips get higher score than history learning outcomes of students who use direct instructional model, (2) there is an interaction effect between instructional models and interpersonal intelligence, (3) History learning outcomes of students who use instructional model Talking Chips with high interpersonal intelligence get higher score than students who use direct instructional model with high interpersonal intelligence, (4) History learning outcomes who use instructional model Talking Chips with low interpersonal intelligence get lower score than students who use direct instructional model with low interpersonal intelligence.